Application of Remote Sensing for Long-Term Analysis of Environmental Criticality Indices in Kendari City - Septianto Aldiansyah; Amniar Ati; Fitriyani Saudi (Jurnal Meteorologi dan Geofisika, 2026)
The decline in vegetation cover has a crucial impact on ecological quality and function, as seen on critical land. Kendari City experiences fairly rapid population growth, being the capital of Southeast Sulawesi Province. This study analyzes long-term changes in Kendari City's environmental quality using the Environmental Criticality Index (ECI) derived from Multitemporal Landsat Satellite Imagery. Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST) can provide information on environmental criticality through the contrast difference between vegetation as a cooling agent and surface temperature, which is often amplified by built-up areas. The results of the study show that the concentration of ECI occurs in the city center area that stretches along Kendari Bay. The moderate ECI experienced regional fluctuations in the 1991-2002, 2001-2014, and 2014-2023 periods, namely -8.43%, +2.28%, and -20.35%, respectively. Meanwhile, the high class experienced gradual expansion, namely +3.38%, +5.12%, and +1.03%, respectively. The 2001-2014 period was the peak phase of ECI changes, with a tendency for environmental quality to decline. The Urban-Rural Gradient shows that the highest ECI value occurs in urban areas and decreases as it moves towards the suburbs, where there are still rural areas. The correlation test shows a strong relationship between them and indicates a significant influence on ECI. These findings underscore the importance of sustainable reforestation strategies in reducing urban environmental pressures.